Efficacy and Safety of the Mosquitocidal Drug Ivermectin to Prevent Malaria Transmission After Treatment: A Double-Blind, Randomized, Clinical Trial. (19th November 2014) - Ouédraogo, André Lin; Bastiaens, Guido J. H.; Tiono, Alfred B.; Guelbéogo, Wamdaogo M.; Kobylinski, Kevin C.; Ouédraogo, Alphonse; Barry, Aïssata; Bougouma, Edith C.; Nebie, Issa; Ouattara, Maurice San; Lanke, Kjerstin H. W.; Fleckenstein, Lawrence; et al.
Abstract : Combining the antimalarial artemether-lumefantrine and the mosquitocidal drug ivermectin is safe and significantly reduces survival of 2 major malaria vectors, Anopheles gambiae and Anopheles funestus . The mosquitocidal effect depends on ivermectin plasma concentration and is related to body mass index. Abstract: Background.  Artemisinin combination therapy effectively clears asexual malaria parasites and immature gametocytes but does not prevent posttreatment malaria transmission. Ivermectin (IVM) may reduce malaria transmission by killing mosquitoes that take blood meals from IVM-treated humans. Methods.  In this double-blind, placebo-controlled trial, 120 asymptomatic Plasmodium falciparum parasite carriers were randomized to receive artemether-lumefantrine (AL) plus placebo or AL plus a single or repeated dose (200 µg/kg) of ivermectin (AL-IVM1 and AL-IVM2, respectively). Mosquito membrane feeding was performed 1, 3, and 7 days after initiation of treatment to determine Anopheles gambiae and Anopheles funestus survival and infection rates. Results.  The AL-IVM combination was well tolerated. IVM resulted in a 4- to 7-fold increased mortality in mosquitoes feeding 1 day after IVM ( P < .001). Day 7 IVM plasma levels were positively associated with body mass index ( r = 0.57, P < .001) and were higher in female participants ( P = .003), for whom An. gambiae mosquito mortality was increased until 7 days after a single dose of IVM (hazard rate ratio, 1.34 [95% confidence interval, 1.07–1.69]; P = .012). Although we found no evidence that IVM reduced Plasmodium infection rates among surviving mosquitoes, the mosquitocidal effect of AL-IVM1 and AL-IVM2 resulted in 27% and 35% reductions, respectively, in estimated malaria transmission potential during the first week after initiation of treatment. Conclusions.  We conclude that IVM can be safely given in combination with AL and can reduce the likelihood of malaria transmission by reducing the life span of feeding mosquitoes. Clinical Trials Registration.  NCT0160325.